(untitled) (ARQUISUR Revista, 2023)
This work reflects on high-rise buildings constructed in Mendoza along the twentieth century by articulating two approaches: on the one hand, it addresses the legal aspect to analyze to what extent the physical-environmental characteristics of the city have defined and/or limited local regulations; and, on the other hand, it enquires into the architectural trends that have influenced the formal and material conformation of the existing high-rise buildings. Based on a chronological tour through building regulations, reference and iconic cases in the city are analyzed. Until the mid-20th century, there was a formal homogeneity that was interrupted by the spread of horizontal property. With the application of the latest regulations, however, it is possible to notice a favorable relationship between buildings and the rest of the factors of the urban system. Many buildings were probably influenced by European modernist trends. Nevertheless, it is possible to identify high-rise architecture designed in close connection to the cultural and environmental context of its urban surroundings.